Rac1 Impairs Forgetting-Induced Cellular Plasticity in Mushroom Body Output Neurons - Cervantes-Sandoval, Isaac; Davis, Ronald L.; Berry, Jacob A. (Frontiers in Cellular Neuroscience, 2020)
Active memory forgetting is a well-regulated biological processed thought to be adaptive and allowing proper cognitive functions. Recent efforts have elucidated several molecular players involved in the regulation of olfactory forgetting in Drosophila, including the small G protein Rac1, the dopamine receptor DAMB and the scaffold protein Scribble. Similarly, we recently reported that dopaminergic neurons mediate both learning and forgetting induced plasticity in the mushroom body output neuron MBON-γ2α’1. Two open questions remain, how does forgetting affect plasticity in other, highly plastic, mushroom body compartments and how do genes that regulate forgetting affect this cellular plasticity. Here we show that forgetting reverses, short-term synaptic depression induced by aversive conditioning in the highly plastic mushroom body output neuron MBON-γ1pedc>α/β. In addition, our results indicate that genetic tampering with normal forgetting by inhibition of small G protein Rac1 impairs restoration of depressed odor responses to learned odor by intrinsic forgetting through time passing and forgetting induced acutely by shock stimulation after conditioning or reversal learning. These data further indicate that some forms of forgetting truly erase physiological changes generated by memory encoding.